LEXICAL innovation and Latin philosophical vocabulary: from Cicero to Boethius - Dowson, C (2020)
This thesis studies the related linguistic phenomena of ‘lexical innovation’ and ‘lexical augmentation’ in selected Latin authors who translated Greek philosophical terminology between the Late Republican era to the sixth century A.D. It is the first kind of comparative study of philosophical lexicalisation in Latin, collating and evaluating lexical data from the corpora of influential Latin authors, using a blend of synchronic and diachronic analyses. One of the arguments of the thesis is the bifurcated tradition of Greco-Roman intellectual thought: one, a continuous transmission of philosophical expression in Ancient Greek from Plato to Byzantium in the East; another, a process of renovation and synthesis, principally from the first century B.C. with authors such as Titus Lucretius Carus and Marcus Tullius Cicero. The findings suggest that the philosophical vocabulary of the Greeks was redefined through the creative literary projects of Latin intellectuals, forging their own terms within the linguistic, stylistic, and conceptual parameters of their language’s grammar. This ‘refraction’ of thought carried far-reaching consequences for early Christian authors and the Scholastic movement of the Middle Ages. To understand the emergence of ‘philosophical Latin’, it is important to note that the development of this technical vocabulary comprised an ensemble of semantic and morpho-syntactic strategies: linguistic practices that engendered the expansion of philosophical expression, (neologism, calques, semantic extensions, and loan-words, among others). The analysis begins with an overview of past scholarship, contextualising this work in the light of modern linguistic and translation theories on the topic, which provide the rationale for the arguments advanced throughout the thesis. The structure is divided over five chapters based around qualitative and quantitative analyses of Latin philosophical terms introduced as the result of translations from Greek terms. This relies on specified criteria applied to new terms and meanings first attested in a given author; that is, there must be some textual ‘signalling’ (such as glossing or direct translation) to indicate certain Latin terms or meanings correspond with Greek ones. These analyses are applied using a case-study approach, beginning with Lucretius and Cicero, then Seneca the Younger, Apuleius, Tertullian, Calcidius, and concluding with Boethius. Within the analyses of Cicero’s and Apuleius’ philosophical works, there are additional selective linguistic commentaries, first on Cicero’s translation of Plato’s Timaeus dialogue in Chapter One followed by Apuleius’ De Platone et Eius Dogmate and his translation of the Pseudo-Aristotelian De Mundo in Chapter Three. The study is accompanied by four sets of appendices for reference, collating and summarising the findings of this thesis.